2008
DOI: 10.1080/17549500701834690
|View full text |Cite
|
Sign up to set email alerts
|

The ICF-CY and children with communication disabilities

Abstract: The International Classification of Functioning, Disability and Health Children and Youth Version (ICF-CY) (World Health Organization, 2007) provides a relevant framework for consideration of children with communication disability by professionals such as speech-language pathologists and audiologists. This paper describes the international and interdisciplinary context in which the ICF-CY was created; then focuses on three major considerations in the development of the ICF-CY: the inclusion of universal pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(39 citation statements)
references
References 42 publications
1
36
0
2
Order By: Relevance
“…A study by McLeod and Threats (10) states that developing countries spend a lot of resources to address food and infrastructure issues. Thus, establishing new partnerships and strategies that favor language, in order to contribute to the quality of life of society, is an important justification for health care and assistance in an comprehensive and humanized way.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by McLeod and Threats (10) states that developing countries spend a lot of resources to address food and infrastructure issues. Thus, establishing new partnerships and strategies that favor language, in order to contribute to the quality of life of society, is an important justification for health care and assistance in an comprehensive and humanized way.…”
Section: Discussionmentioning
confidence: 99%
“…The International Classification of Functioning, Disability and Health -Children and Youth Version (ICF-CY) 1(8) derived from the ICF in response to the need and diversity of disabilities regarding their nature, intensity, and the impact they can have throughout the long period of child growth and development (9)(10)(11)(12) . The national literature that makes use of the ICF-CY is scarce, and one of the first publications (13) in the field of Speech-Language Pathology based on the ICF-CY is aimed at children with cochlear implants and presents important questions for audiological practice.…”
Section: Introductionmentioning
confidence: 99%
“…Within a social framework, SLPs investigate beyond the child's difficulties to consider holistically the factors, both personal and environmental, that contribute to, and impact on, a child's life (Duchan, 2001). The International Classification of Functioning, Disability and Health-Children and Youth version (WHO, 2007) is a framework that incorporates information about the child's body structure, functioning, participation, environmental and personal factors (McLeod & Threats, 2008). Consideration of each of these factors is especially important when working with children from culturally and linguistically diverse (CALD) backgrounds, such as Indigenous children, since social factors, including dialect, community and the notion of typical, may differ from those of the SLP (Crago, 1992;Ball & Bernhardt, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has demonstrated the successful application of the framework for describing the functioning of children with speech and language disorders, yet none specifically address social communication [20,[24][25][26][27][28][29]. Further, Castro and colleagues [30,31] have demonstrated the ICF-CY's utility both in linking existing measures of autism to its functional dimensions, and to special education curriculum for preschoolers for purposes of authentic assessment [32].…”
Section: The Icf-cy Framework and Social Communicationmentioning
confidence: 99%
“…Recent reviews of language assessment tools from an ICF perspective revealed that only the single domain of Body Functions and Structures [28,37] is well covered. Notably 'communication participation' in real-life situations is not represented [37,38].…”
Section: The Icf-cy Framework and Social Communicationmentioning
confidence: 99%